The forearm fillet flap: ‘spare parts’ reconstruction for forequarter amputations(*) - Ayyala, Haripriya S. (Case Reports Plast Surg Hand Surg, 2019)
Radical forequarter amputation is often performed for recurrent proximal extremity tumors. A free forearm fillet flap is used to provide excellent coverage of the resultant defect without donor site morbidity. Use of a free flap from the distal portion of the extremity with proximal tumor burden is safe and effective.